Decrease Regional Income in the Tourism Sector of West Sulawesi Province During COVID-19 Pandemic - Awal Nopriyanto Bahasoan; Wulan Ayuandiani; Muhammad Mukhram; Farida Millias Tuty (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine decrease regional income in the tourism sector of West Sulawesi Province during coronavirus disease (COVID-19) pandemic. The researcher tries to describe what is understood and described by the research subject. Then the qualitative approach was chosen using a descriptive method and this type of research used library research, namely the research was carried out by searching the literature (library) in the form of books, notes, and reports on research results from previous studies. Data analysis in qualitative research is carried out simultaneously with the data collection process. The impact of COVID-19 pandemic greatly affects the decline in regional income and employee performance in the tourism sector. During COVID-19 pandemic, the more it will affect the decline in tourism income and decrease employee performance. The most dominant employee performance indicator is contextual performance. The temporary closure of tourist attractions and entertainment has a negative impact on employee performance such as reduction of employees, cuts in wages and layoffs. The most dominant indicator of tourism and entertainment income is the amount of local revenue from the tourism and entertainment tax sector. The income of tourist attractions has decreased, so it has an effect on decreasing the performance of tourism employees.